Juzgamiento en ausencia del infractor en delitos de narcotráfico. - Rodriguez Ramos, Eduardo Alfredo (2011)
The drug trade has been one of the biggest current topics at national and international level; it is considerate as the end of lucre to elevate economic indices, acquisition of goods and services. The firs criminal activities drug dealer showed in the societies like smuggling of certain substances like: It happened in the old china with the trade of the opium, these were used as medicine and for the addiction it became prohibited by the authorities, and for the reasons of illegal transport. The drug traffic has reached a high level in the different social branches. As for people that carry out these activities they are considered as drug dealers, they are devoted to the commercialization of these substances giving a danger result to the society where we live, it affects to health, economy and deferments parts of the societies. Therefore many of these offenders continue to be dedicated to this activity and what is thought to implant a system or to improve the current, one to stop this activity, by all means. The judgment in this offender’s absence in crimes of drug trade has considered that the penalty action doesn´t prescribe in these crimes. Since our legislation these crimes are prescript able having in all that the Art 88 of the Law of Substances narcotics and psychotropic. Apparent the penalty action prescribes double the maximum pain for these crimes and the pain in turn in double of the time condemnation; many of these trades are fugitive of the justice because they are absent so that the penalty action prescribes and their absence cause damage an danger to other societies. The relevance for it is settling down improvements to the law with the only end how to stop the drug trade. Being the holders of this crime the good know drug dealers as bosses of the mafia, they deceive the juridical system to continue with their criminal activity.